Comparative Study of Certain Physiological Parameters Between Elderly People Who Practice Physical Activity and Those Who Do Not - Sebai , Mohamed Lamine; Benhadid, Youcef (sports creativity, 2025)
The overall objective of this research is to examine the conditions under which maintaining a physically active lifestyle helps preserve and even develop physiological capacities affected by aging. We therefore evaluated certain physiological parameters in individuals over 50 years of age (resting heart rate and resting blood pressure) to demonstrate the degree of influence of physical activity on their cardiovascular system. Our sample consisted of 12 older adults who regularly engaged in physical activity and 12 older adults who did not. The main results highlighted a beneficial effect of physical activity on the aging body and confirmed that a sedentary lifestyle is a contributing factor to the decline in cardiovascular capacity in older adults.